2008
DOI: 10.1097/jsm.0b013e31817e34f8
|View full text |Cite
|
Sign up to set email alerts
|

Mononucleosis and Athletic Participation: An Evidence-Based Subject Review

Abstract: Infectious mononucleosis (IM) is a common medical condition that afflicts thousands of young athletes each year. Despite the self-limited nature of this disorder, the variability of the clinical presentation and the rare risk of splenic rupture routinely present sports medicine clinicians with difficult return-to-play decisions. Currently there are no evidence-based guidelines regarding the management of the athlete with IM. This review discusses the available research data pertaining to the management of IM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 55 publications
1
78
0
2
Order By: Relevance
“…Bed rest is unnecessary, but contact sports are contraindicated (10,46,127,163). Patients generally adjust daily activities to the level of their exercise tolerance.…”
Section: Treatment Symptomatic Management Of Infectious Mononucleosismentioning
confidence: 99%
See 1 more Smart Citation
“…Bed rest is unnecessary, but contact sports are contraindicated (10,46,127,163). Patients generally adjust daily activities to the level of their exercise tolerance.…”
Section: Treatment Symptomatic Management Of Infectious Mononucleosismentioning
confidence: 99%
“…There is no consensus. A recent evidence-based review suggested that they may return as early as 3 weeks after the onset of illness provided that they are afebrile, have no remaining clinical symptoms, and have normal energy (163).…”
Section: Treatment Symptomatic Management Of Infectious Mononucleosismentioning
confidence: 99%
“…This calls into question the reliability of such examination, especially when the risk of splenic rupture, albeit rare, is on the table (31)(32)(33)(34). Because of this the benefits of imaging, such as ultrasound (US) or computed tomography (CT) are seen and allow for the best counseling of your young athlete.…”
Section: Examinationmentioning
confidence: 99%
“…The question then becomes, "who do I image?" Knowing the pitfalls of physical examination, any athlete you are caring for who has an illness or medical process that causes splenomegaly should be imaged if your index of suspicion is high as even light, noncontact, activities should be avoided initially (32). Imaging is not required for limiting participation, especially in IM as participation should be limited after the diagnosis is made.…”
Section: Examinationmentioning
confidence: 99%
See 1 more Smart Citation